Censo 2020 – novas Macrorregiões, 50 anos depois - José Donizete Cazzolato (Confins)
Revisiting the argumentation put forth in 2007 in his study The Post-Tocantins Brazilian Regions: Drafting a New Arrangement, the author summarizes two of its chapters: Creation of Tocantins State and Rupture with the Model in Force and The Official Regionalization of Brazil. Considerations about the geographic framework of the country’s northern strip are re-examined, highlighting elements indicative of formation and densification of the new regional hub situated at the Pará–Maranhão–Tocantins junction. Territorial non-conformities in the current regional design are brought to light, and the advantages of the author’s proposal are demonstrated with the aid of maps—namely, assignment of Maranhão to the North Region and creation of a novel unit: the Northwest Region. The report concludes addressing points of legal controversy involving the Instituto Brasileiro de Geografia e Estatística (IBGE) and the legal competencies required for implementing the proposed changes.